Pengurusan Zakat Asnaf Mualaf di Negeri Johor: Satu Sorotan - Sahalan, Othman; Hj Abdullah, Luqman (Jurnal Fiqh, 2014)
The converts are among those who are eligible to receive zakat. The effectiveness of zakat institutions in managing the charity?s funds will ensure the objectives of charity that aim to make them steadfast and devoted, and maintain their religious commitment to Islam. In the Malaysian context, the management of the charity is under state charity institutions. This article looks at the management of the charity by the Johore Islamic Council. It reviews the existing problems in the management and also the extent of help that this charity provides to the converts. Jurists debate the rights of the converts, and the programmes implemented by Majlis Agama Islam Johor that are associated with this group are analysed. The findings highlight the areas of improvement needed in the management of the rights of converts. This study is based on qualitative research through the analysis of documents obtained from various sources, including the Ukhuwwah Unit, the Johor Religious Department and interviews with officials. The study revealed that substantial allocations are devoted to the development of these recipients. What can be concluded is that the role of the Johor Islamic Religious Council and all parties of authority in managing the conversion in Johor must be strengthened in order to achieve the main objective of distribution of alms to the converts, which is "ta'lif al-qulub".